Optimal irrigation amount can increase cotton lint yield by improving canopy structure and microenvironment under non-film deep drip irrigation. (1st August 2022) - Li, Nannan; Li, Junhong; Tung, Shahbaz Atta; Shi, Xiaojuan; Hao, Xianzhe; Shi, Feng; Wahid, Muhammad Ashfaq; Ali, Basharat; Rashid, Rida; Wang, Jun; Luo, Honghai
Abstract: In the arid region of Northwest China, exploring the feasibility of using non-film deep drip irrigation (DDI) instead of film drip irrigation to solve the problem of residual film pollution is an urgent task. Therefore, in this study, we hypothesized that efficient and clean production can be achieved by optimizing the irrigation amount of non-film cotton, thus improving the canopy environment and increasing the accumulation and distribution of biomass. A 2-year field experiment was performed to compare the cotton canopy microenvironment, biomass accumulation, lint cotton yield and fibre quality attributes under various irrigation levels. The experiment was arranged in a randomized complete block design with five irrigation amount treatments (m 3 ha −1 ): 2649 (W1 ); 2925 (W2 ); 3201 (W3 ); 3477 (W4 ); and 3753 (W5 ). The results revealed that an increase in the irrigation amount decreased the transmittance of canopy photosynthetically active radiation (PAR) by 4.1–18.7%, while the cotton plant biomass (CPB) and reproductive organ biomass (ROB) were significantly increased by 7.6–5.9% and 22.0–54.1%, respectively. The fibre quality did not differ significantly among treatments. Moreover, under the W4 treatment, the leaf area index (LAI), mean tilt angle (MTA), canopy humidity and cotton lint yield were increased by 1.4–22.3%, 0.3–8.7%, 0.6–2.9% and 4.4–18.7%, respectively, and the canopy temperature was decreased by 0.2–2.2% as compared to the other treatments. The lint cotton yield was negatively correlated with the canopy humidity from the initial squaring stage to the full boll stage. This comprehensive evaluative analysis suggests that the optimal irrigation amount of non-film cotton is 3477 m 3 ha −1 under the studied conditions, and this irrigation method is recommended as an alternative to film drip irrigation as it allows cotton to be planted without worrying about plastic pollution in irrigated agricultural areas. This study enriches the high-efficiency cotton planting technologies of non-film DDI and provides scientific guidance for the further popularization and application of non-film cotton. Graphical abstract: Fig. 1 Graphical abstract illustrating the whole theme of the study. Image 1 Highlights: Deep-drip irrigation (DDI) can compensate the negative effects of non-film cotton cultivation on the canopy structure. Increasing irrigation amount increased the leaf area index and mean tilt angle under DDI. Lint cotton yield depends on the photosynthetically active radiation in the upper and middle canopy under DDI. DDI without plastic mulching has the potential to replace mulched drip irrigation.